Economic incentives and social preferences: A reference-based Lucas critique of public policy - Samuel Bowles; Sandra Polanía Reyes (University of Massachusetts, Department of Economics, 2009)
Policies and explicit incentives designed for self-regarding individuals sometimes are less effective or even counterproductive when they diminish altruism, ethical norms and other social preferences. Evidence from 51 experimental studies indicates that this crowding out effect is pervasive, and that crowding in also occurs. A model in which self-regarding and social preferences may be either substitutes or complements is developed and evidence for the mechanisms underlying this non-additivity feature of preferences is provided. The result is a preference-based analogue to the Lucas Critique restricting feasible implementation to allocations that are supportable given the effect of incentives on preferences.
Keywords: D64; H41; D78; Z13; 330; public goods; behavioral experiments; social preferences; second best; motivational crowding; explicit incentives